A case study of English/Xhosa code switching as a communicative and learning resource in an English medium classroom - Marawu, Sithembele (Rhodes University, Faculty of Education, Department of Education, 1997)
Research on code switching (CS), the use of more than one language in a single piece of discourse, has focused on various aspects of the phenomenon. For example, research has concentrated on switching that occurs between turns of interlocutors in a piece of discourse, sometimes between sentences within a single tum and sometimes within a sentence. Researchers have approached this discourse behaviour from various perspectives. For instance, some investigate the social functions of the switches, others explore the linguistic constraints on the switches. Furthermore, most of this research has examined CS in non-educational contexts. Research on classroom CS, the focus of this study, took hold in the mid 1970s. Researchers began to investigate the communicative functions of CS and the frequency with which teachers and learners used certain languages to perform different functions. Recent studies on classroom CS focus on the sequential flow of classroom discourse and "the way in which codeswitching contributes to the interactional work that teachers and learners do in bilingual classrooms" (Martin-Jones 1995:91). The approach used in these studies is the conversational analytic approach grounded in ethnographic observation. In South Africa little research has been done on classroom CS, though it makes an important contribution to the interactional work of teachers and learners in classrooms. This study explores the use of English and Xhosa in the classroom as a learning and communicative resource. Its focus is on the communicative functions of the switching behaviour of a teacher as she interacts with her pupils. In other words, this study looks at how the research subject uses English and Xhosa to get things done in the classroom. As the classroom situation observed is dominated by the teacher, this study concentrates mainly on her communicative repertoire. It does not attempt a full linguistic description of the switches made by the research subject, for example, it does not deal with linguistic constraints on CS. One of the major findings noted in this study is that the research subject does not use CS so as to avoid using English. She uses CS as a learning resource. It has also been noted that CS is used by the research subject as a contextualisation cue, for example, we noted the way it co-occurs with other contextualisation cues like nonverbal communication cues. This is in line with Martin-Jones' (1995) viewpoint that CS is not used by bilingual teachers simply to express solidarity with the learners but to negotiate and renegotiate meaning.
Keywords: Code switching (Linguistics) -- South Africa; Language and education -- South Africa; Education, Bilingual -- South Africa